An Assessment on Bat Diversity in Curitiba, Paraná State, Subtropical Brazil - Gledson Vigiano Bianconi; Michel Miretzki (Brazilian Archives of Biology and Technology, 2021)
Abstract Urbanization changes natural environments making them inhospitable to autochthonous fauna. However, studies have shown that certain groups and animal species tolerate urban habitat or even benefit from it as is the case of some bats. This study assesses the diversity of bats in Curitiba, Southern Brazil, providing a basis for the discussion on their conservation, management, ecological services provide, and the critical evaluation of their role in the zoonoses of interest for public health. The data was compiled from a combination of museum, historical and recent literature (1824 to 2020), records to identify which bat species have actually been captured or recorded in Curitiba. The results indicate 29 species (five of them threatened with extinction) from four families: Phyllostomidae, Noctilionidae, Molossidae and Vespertilionidae. Insectivorous bats (Molossidae and Vespertilionidae) represent 62.1% of the species recorded; and the primarily frugivorous (Phyllostomidae) 24.1%, followed by nectarivorous/polinivorous species (6.9%), insectivorous/frugivorous (ca. 3.4%) and piscivorous/insectivorous (ca. 3.4%). Fruit-eating batsseem to prefer urban green areas while insectivores tend to occupy human-made structures. Our results show that this high-growth potential diversity bears both a numerical and ecological relevance. It is worth remembering that Curitiba is in Brazil’s subtropical area, where the richness of bat species is lower, and the predominant species are different from those in the tropical region of the country. Finally, studies on the natural history of bats (feeding, reproduction, roosting, etc.) in Curitiba are scarce and urgently necessary given to the current pandemic scenario where these traditionally stigmatized animals have been even more depreciated by public opinion.